STUDY OF THE BENEFITS OF PHYSICAL EXERCISE IN PHYSICAL PROBLEMS OF WOMEN - Sidhu, Sandeep; Gautam, Priyanka (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Amidst the changing social environment, today women have become more ambitious than before. Whether it is about their future or someone else’s, today the role of women has become completely different from their traditional role of housewives or mother-daughter. Today women have come out of the four walls and are playing an equal role in the decisions being taken in the socio-economic and political field. However, for women to properly discharge all their roles, it is important that they have good health, mental peace and balance in life. Today we have many training programs available. Which are prepared scientifically. The main components of a training program are the amount, intensity, and frequency of exercise sessions. We exercise to maintain our health and under exercise we can adopt aerobic exercise. Aerobic exercise is a type of cardiovascular conditioning or cardio. Under this, fitness can be maintained properly by including activities like brisk walking, swimming, running or cycling in our daily lives.